Poetry of Michelangelo : an Introduction. - Ryan, Chris (Continuum International Pub. Group, 2000)
One of the greatest artists of all time, Michelangelo's work as a poet has been unjustly ignored. This thorough introduction outlines the broad chronological evolution of the poems, includes the poetry in both the original Italian and in translation and explores the themes raised in the poems.